Yersinia adhesins: An arsenal for infection. Issue 9 (17th May 2016) - Chauhan, Nandini; Wrobel, Agnieszka; Skurnik, Mikael; Leo, Jack C.
Abstract : The Yersiniae are a group of Gram‐negative coccobacilli inhabiting a wide range of habitats. The genus harbors three recognized human pathogens: Y. enterocolitica and Y. pseudotuberculosis, which both cause gastrointestinal disease, and Y. pestis, the causative agent of plague. These three organisms have served as models for a number of aspects of infection biology, including adhesion, immune evasion, evolution of pathogenic traits, and retracing the course of ancient pandemics. The virulence of the pathogenic Y ersiniae is heavily dependent on a number of adhesin molecules. Some of these, such as the Yersinia adhesin A and invasin of the enteropathogenic species, and the pH 6 antigen of Y. pestis, have been extensively studied. However, genomic sequencing has uncovered a host of other adhesins present in these organisms, the functions of which are only starting to be investigated. Here, we review the current state of knowledge on the adhesin molecules present in the Yersiniae, and their functions and putative roles in the infection process.